Late postoperative choroidal detachment following an uneventful cataract surgery in a patient on topical latanoprost. (14th July 2015) - Krishnamurthy, Rashmi; Senthil, Sirisha; Garudadri, Chandrasekhar S
Abstract : Topical latanoprost is a most effective and commonly used antiglaucoma medication. Use of prostaglandin analogues (PGA) in the early postoperative period is controversial due to its proinflammatory properties. We report a case of a 64-year-old man with primary open angle glaucoma, post-trabeculectomy 17 years prior, with good intraocular pressure (IOP) control on topical levobunolol 0.5% and latanoprost 0.005%. He underwent a clear corneal phacoemulsification surgery in his left eye and the PGA was stopped. He had an uneventful postoperative course and was prescribed eyeglasses at 4-week follow-up. Two weeks later, he presented to the emergency department with decreased vision in the left eye, flat anterior chamber, IOP of 00 mm Hg and 360° choroidal detachment. The continued use of topical latanoprost in the operated eye was implicated as the cause. This case illustrates the serious vision-threatening side effect of PGA when used in the early postoperative period.